Ceria/silicon carbide core–shell materials prepared by miniemulsion technique - Borchardt, Lars; Oschatz, Martin; Frind, Robert; Kockrick, Emanuel; Lohe, Martin R.; Hauser, Christoph P.; Weiss, Clemens K.; Landfester, Katharina; Büchner, Bernd; Kaskel, Stefan (Beilstein Journal of Nanotechnology, 2011)
For the first time we present the synthesis of CeO2/Si(O)C core–shell particles prepared by the miniemulsion technique. The Si(O)C core was obtained by means of a polycarbosilane precursor (SMP10), which was subsequently functionalized with ceria and pyrolyzed to the ceramic. The size of these particles could easily be adjusted by varying the surfactants and the surfactant concentration, or by the addition of comonomers. Hence particle sizes ranged from 100 to 1000 nm, tunable by the preparation conditions. All materials were characterized by photon cross correlation spectroscopy, scanning electron microscopy and elemental mapping investigations. Furthermore, first catalytic tests were carried out by temperature programmed oxidation (TPO) of methane, and the activity of this material in lowering the onset temperature of methane combustion by 262 K was documented.
Keywords: ceria; cerium dioxide; core shell; miniemulsion; oxycarbide; silicon carbide; TPO catalytic